2020
DOI: 10.1186/s12877-020-01886-0
|View full text |Cite
|
Sign up to set email alerts
|

Measuring global functioning in older adults with cognitive impairments using the Rasch model

Abstract: Background Cognitive and functional measures are often measured and interpreted separately during the clinical evaluation of patients with cognitive impairment. This can sometimes lead to a challenging interpretation when measures do not show concordance, especially after a clinical intervention. In this study, the development and evaluation of a new approach, using the Rasch model, that combines cognitive and functional measures in one single and more powerful measure (compared to stand-alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For example, in the NHANES cohort, a z-score of zero is equivalent to the mean of the 643 participants, and a z-score of 1.0 indicates a value that is one standard deviation above the mean performance. A single cognitive score provides a better measure of global cognitive function than individual scores for clinical evaluation of patients with cognitive impairment, especially when individual test scores do not show concordance (Mistridis et al, 2015;Palumbo et al, 2020).…”
Section: Cognitive Performancementioning
confidence: 99%
“…For example, in the NHANES cohort, a z-score of zero is equivalent to the mean of the 643 participants, and a z-score of 1.0 indicates a value that is one standard deviation above the mean performance. A single cognitive score provides a better measure of global cognitive function than individual scores for clinical evaluation of patients with cognitive impairment, especially when individual test scores do not show concordance (Mistridis et al, 2015;Palumbo et al, 2020).…”
Section: Cognitive Performancementioning
confidence: 99%
“…Therefore, to obtain a good data analysis of survey questionnaire, a statistical software for Rasch model analysis named Winstep software V3.72.3 was used. Literature studies showed that the Rasch model has been used in other research fields such as education [32]- [36], food and beverages [23], [37], medical [24], and sport [38] and it was proven capable to measure any subjective assessment. At the same time, Rasch is also capable to convert all ordinal data into ratio data.…”
Section: Discussionmentioning
confidence: 99%
“…Rasch model is a common probabilistic model that measures the latent traits on a linear scale using log odds by identifying the location of items and respondents [23]. Furthermore, it is a hierarchical order of each item constructed on a level of complexity, including an ability score for each subject [24]. Rasch Model functions with the measurement of respondent's response to items, using the same scale at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the radial structure of the WMTs is not a multiplication of possibilities, like over-used typical cognitive tests. The point is that WMTs effectively conduct and generate Cognitive tractography requires physicists who know how cognitive-affective processes currently follow Lisa Feldman-Barret's "cooking recipe ingredients" models [46], the applications of Bayesian techniques by Poldrack [47], the variations of parameters that make up the Rasch with the cognitive tractography [48]. Cognitive ontologies and Diffusion Data area headache in words of their supporters (see Figure 25).…”
Section: Discussionmentioning
confidence: 99%